2019
DOI: 10.3390/molecules24203767
|View full text |Cite
|
Sign up to set email alerts
|

Sciadopitys verticillata Resin: Volatile Components and Impact on Plant Pathogenic and Foodborne Bacteria

Abstract: Sciadopitys verticillata (Sv) produces a white, sticky, latex-like resin with antimicrobial properties. The aims of this research were to evaluate the effects of this resin (Sv resin) on bacterial populations and to determine the impact of its primary volatile components on bioactivity. The impact of sample treatment on chemical composition of Sv resin was analyzed using Fourier transform infrared spectroscopy (FTIR) coupled with principal component analysis. The presence and concentration of volatiles in lyop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Tricyclene, a tricyclic monoterpene, is a valuable product that naturally occurs in the essential oils of a number of plant species, such as Salvia aegyptiaca [3], Polyalthia suberosa [4], and Elettaria cardamomum [5]. It was reported that plant essential oils rich in tricyclene have antioxidant [5], antitumor [4], and antimicrobial [5][6][7] properties. Meanwhile, it has been reported that the essential oil derived from Agathis robusta bark, which is abundant in tricyclene, exhibits potential efficacy against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Tricyclene, a tricyclic monoterpene, is a valuable product that naturally occurs in the essential oils of a number of plant species, such as Salvia aegyptiaca [3], Polyalthia suberosa [4], and Elettaria cardamomum [5]. It was reported that plant essential oils rich in tricyclene have antioxidant [5], antitumor [4], and antimicrobial [5][6][7] properties. Meanwhile, it has been reported that the essential oil derived from Agathis robusta bark, which is abundant in tricyclene, exhibits potential efficacy against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…8,15,17,20 The resin that became Baltic amber is generally accepted to have been produced by extinct pines of the family Sciadopityaceae. 13,[21][22][23][24] One species of this family is extant:…”
mentioning
confidence: 99%
“…Sciadopitys verticillata (Thunberg) Siebold and Zuccarini, also known as the Japanese umbrella pine because it is an evergreen conifer with cladodes arranged in whorls, and is indigenous to Japan. 21,22,[25][26][27] S. verticillata produces a white resin that exhibits the aforementioned "Baltic shoulder" feature in IR spectra; 13,[21][22][23] furthermore, inclusions of cladodes characteristic of Sciadopityaceae have been found in samples of Baltic amber. 24 An unmet need exists for new chemical matter to target resistant bacterial infections, as well as inflammation and pain resulting from a variety of disease modalities; however, identification of new therapeutic scaffolds remains nontrivial.…”
mentioning
confidence: 99%